O papel do fogo na estruturação funcional e filogenética de savanas e florestas tropicais - Dantas, Vinícius de Lima (Universidade Federal de São Carlos, 2014)
The savanna is a major biome covering one six of the Earth land surface. Its origin in the late Miocene seems to be tightly related to an increase in fire frequencies, promoting the spread of savannas and grasslands over areas previously dominated by forest vegetation. Fire has also been pointed out as an important factor regulating the current distribution of tropical savanna and forest biomes. Thus, it is impossible to fully understand the temporal dynamics of these biomes without knowledge on the mechanisms by which fire interacts with the environment and with plant traits to shape community assembly in the tropics. Thus, we focused in three broad questions related to the fire ecology of savanna and forest biomes: (1) What is the role of fire in structuring trait variability in savannas? (2) What is the role of fire in regulating the distribution of tropical savanna and forest biomes? (3) What are the main predictors of community assembly in fire filtered savannas and by which mechanisms they operate? To answer these questions we collected field data on plant traits measured at the individual level, soil and topographic information in Emas National Park (central Brazil) and obtained fire history information from remote sensing data. We used such data to test specific models about the dynamics of the vegetation in savanna and forest biomes. Our studies allowed us to conclude that: (1) Mesic savannas are fire-filtered in the sense that the variations in fire frequency currently observed in these savannas do not explain large fractions of the functional diversity and of the community assembly. (2) In the wet tropics, savannas and forests are two coexisting stable states with contrasting functional traits and assembly processes, regulated by fire-plant feedbacks. (3) In patchy fire-filtered savannas, community assembly is shaped by water and nutrient availabilities.
Keywords: Ecologia; Estrutura de comunidades; Fogo e ecologia; Ecologia do cerrado; Nicho (Ecologia); Ecologia de comunidades; CIENCIAS BIOLOGICAS::ECOLOGIA